2018
DOI: 10.1002/cam4.1513
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of adult patients with ALL in Mexico City: first report from the Acute Leukemia Workgroup (ALWG) (GTLA)

Abstract: Acute lymphoblastic leukemia (ALL) is a hematologic malignancy characterized by the clonal expansion of hematopoietic lymphoid progenitors. With new target therapies, the survival of adults with ALL has improved in the past few decades. Unfortunately, there are no large ALL patient series in many Latin American countries. Data from the Acute Leukemia Workgroup that includes five Mexico City referral centers were used. Survival was estimated for adult patients with ALL during 2009–2015. In total, 559 adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In our study, the median age was older than that reported in other publications 11,13 and the distribution by gender coincides with other studies, in which these hematological malignancies are more frequent in men. 11,13 Regarding diagnoses, the most frequent was non-Hodgkin’s lymphoma with 54.9% of patients, which contrasts with previously reported results, where the most prevalent diagnosis was acute lymphoblastic leukemia and acute myeloid leukemia respectively. 11,14 However, this can be explained by the distribution of patients treated at our Institute, since 60% of hematology patients seen there each year have a diagnosis of lymphoma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the median age was older than that reported in other publications 11,13 and the distribution by gender coincides with other studies, in which these hematological malignancies are more frequent in men. 11,13 Regarding diagnoses, the most frequent was non-Hodgkin’s lymphoma with 54.9% of patients, which contrasts with previously reported results, where the most prevalent diagnosis was acute lymphoblastic leukemia and acute myeloid leukemia respectively. 11,14 However, this can be explained by the distribution of patients treated at our Institute, since 60% of hematology patients seen there each year have a diagnosis of lymphoma.…”
Section: Discussionsupporting
confidence: 90%
“…As in other contexts as well, often the referral is so late that the death of the patient happens that same day. 12 In our study, the median age was older than that reported in other publications 11,13 and the distribution by gender coincides with other studies, in which these hematological malignancies are more frequent in men. 11,13 Regarding diagnoses, the most frequent was non-Hodgkin's lymphoma with 54.9% of patients, which contrasts with previously reported results, where the most prevalent diagnosis was acute lymphoblastic leukemia and acute myeloid leukemia respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Previous data in this population show a 3-year survival rate of 25.7%, whereas data from our study show a 2-year survival rate of 72.1. 4 , 12 Furthermore, the poor survival in the historical cohort contrasts with the international reports, which show a 5-year OS of 60% in the AYA population either with HyperCVAD or Augmented Berlin-Frankfurt-Munster regimen. 14 In contrast, in the original report that presented the results of the CALGB 10403 regimen, only 15% of the study population were Hispanic (N = 45), and survival outcomes of this subgroup were similar to that of non-Hispanic patients.…”
Section: Discussionmentioning
confidence: 67%
“… 3 A previous multicenter registry gathered data from 559 adults diagnosed with ALL across 5 reference centers in Mexico City and identified adolescents and young adults (AYAs) as the subgroup with the highest incidence, comprising 67.3% of all diagnosed cases. 4 Data retrieved from this registry showcased that most patients were undergoing treatment with traditional adult regimens; the most frequently used was HyperCVAD. In terms of outcomes, the study identified a high treatment-related mortality (17.3%) and poor overall survival (OS) in the general study population (3-year survival rate of 22%) as well as in the AYA subgroup (3-year survival rate of 25.7%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation